Perubahan Komposisi Kimiawi Produk Yogurt dengan Penambahan Kalsium Karbonat pada Kultur Starter Campuran - Safari, Agus; Ghina, Sarah Fahma; Djajasoepena, Sadiah; ', O. Suprijana; Indrawati, Ida; Rachman, Saadah D.; Kamara, Dian S.; Ishmayana, Safri (Jurnal Natur Indonesia, 2016)
Mixed lactic acid bacteria culture is commonly used in yogurt production. In the present study, two lactic acid bacteria (Lactobacillus bulgaricus and Streptococcus thermophillus) was used as starter culture. Calcium carbonate was added to the starter culture to increase the quality of mixed starter culture of L. bulgaricus and S. thermophillus with ratio of 4:1. The present study was directed to investigate the chemical composition of mixed starter culture with and without calcium carbonat addition. Furthermore, the effect of each starter culture on yogurt product chemical composition was also examined. The pH, lactose, soluble protein and acid content was determined as chemical composition parameters. For starter culture without calcium carbonate addition, the yogurt has pH, lactose, soluble protein and acid content of 4.18–4.39, 4.18–4.39% w/v, 2.88–4.36% w/v and 0.82–0.99% w/v, respectively. While for starter culture with calcium carbonate addition, the yogurt product has pH, lactose, soluble protein and acid content of 4.26–4.37, 1.47–1.75% b/v, 3.42–4.95% w/v and 0.86–1.11% w/v, respectively. Addition of 0.05% w/v calcium carbonate to mixed starter culture gave effect on lactose consumption, where it still can convert lactose to lactic acid up to 45 days of storage. Furthermore, the yogurt product made with starter culture with calcium carbonate addition has higher soluble protein content compared to yogurt made with starter culture without calcium carbonate addition